2007
DOI: 10.1016/j.ygcen.2007.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Low salinity acclimation and thyroid hormone metabolizing enzymes in gilthead seabream (Sparus auratus)

Abstract: We investigated the effect of acclimation to low salinity water of gilthead seabream (Sparus auratus), a euryhaline seawater teleost, on the activities of thyroid hormone-metabolizing enzymes in gills, kidney, and liver. Following acclimation to low salinity water, the plasma free thyroxine (T(4)) concentration increases 2.5-fold, and outer ring deiodination activities towards T(4), 3,5,3'-triiodothyronine (T(3)) and 3,3',5'-triiodothyronine (reverse T(3), rT(3)) in the gills are reduced by 20-32%. Conjugation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The notion of intracellular actions of locally produced T 3 also helps explain why plasma fT 3 concentrations were unaltered by cortisol injection. Indeed, osmotic challenges changed peripheral ORD activities in S. senegalensis and Sparus auratus but did not result in altered plasma fT 3 levels (Klaren et al 2007b, Arjona et al 2008. In S. fontinalis, circulating T 4 and T 3 remained unaltered after a cortisol treatment that had increased hepatic T 4 -ORD activities (Vijayan et al 1988).…”
Section: Discussionmentioning
confidence: 94%
“…The notion of intracellular actions of locally produced T 3 also helps explain why plasma fT 3 concentrations were unaltered by cortisol injection. Indeed, osmotic challenges changed peripheral ORD activities in S. senegalensis and Sparus auratus but did not result in altered plasma fT 3 levels (Klaren et al 2007b, Arjona et al 2008. In S. fontinalis, circulating T 4 and T 3 remained unaltered after a cortisol treatment that had increased hepatic T 4 -ORD activities (Vijayan et al 1988).…”
Section: Discussionmentioning
confidence: 94%
“…Indeed TH have been thought to support long-term adaptive responses mediated by growth hormone, prolactin and cortisol, among other classical osmoregulatory messengers (Sakamoto and McCormick, 2006). However, previous studies from our laboratory (Orozco et al, 1998;Orozco et al, 2002b) and recent studies in the seabream gill (Klaren et al, 2007), strongly suggest a more direct involvement of TH in the hydro-osmotic balance in fish. Furthermore, our present results support the suggestion that a putative hypo-osmotic, OREBP-mediated increase in hepatic D2 activity could be an important endocrine component for the maintenance of hydro-osmotic homeostasis in fish.…”
Section: López-bojórquez and Othersmentioning
confidence: 88%
“…TH play a central role in regulating diverse homeostatic functions, from the basal metabolic rate and protein synthesis, to development and cell differentiation (Anderson et al, 2000). Nevertheless, the function of TH in hydro-osmotic balance in fish has been a controversial issue (for reviews, see McCormick, 2001;Orozco and Valverde-R., 2005;Klaren et al, 2007). Previous data from our laboratory have shown that in the euryhaline teleost Fundulus heteroclitus (Fh), hypo-osmotic stress elicits an increase in liver iodothyronine deiodinase type 2 (D2) activity (Orozco et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported species-specific changes in plasma TH levels, ORD activity (Arjona et al, 2008) or deiodinase gene expression (Lorgen et al, 2015) when fish are submitted to an osmotic challenge. Osmotic acclimation in fish is also associated with variations in plasma THs and in gilthead seabream plasma free T4 and gill ORD activity respond to a change in environmental salinity from 35 ppt to 1 ppt (Klaren et al, 2007).…”
Section: Introductionmentioning
confidence: 99%